Lipidomic Assessment of Triacylglycerol and Cholesterol Ester Species After n-3 Polyunsaturated Fatty Acid Suppementation in Humans: Comparison of Response Phenotypes. (29th May 2020) - Picklo, Matthew; Bukowski, Michael; Vallée Marcotte, Bastien; Guénard, Frédéric; Vohl, Marie-Claude
Abstract: Objectives: Assess the differences in triacylglycerol (TAG) and cholesterol ester (CE) species in the plasma of individuals displaying heterogeneous lipid responses following long chain n-3 (LCn-3) polyunsaturated fatty acid supplementation. Methods: We performed a targeted, mass spectrometry (MS), infusion-based lipidomic analysis on plasma samples obtained from a clinical study in which participants were supplemented with 3 g/day of LCn-3 in the form of fish oil capsules over a 6-week period. Triacylglycerol (TAG) species and cholesteryl esters (CE) were quantified for 130 participants pre- and post-supplementation. Results: Based on the change of total TAG concentrations following supplementation, participants were segregated into three response phenotypes: (1) positive responders (R+; TAG decrease < 10%), (2) non-responders (NR; TAG changes +/− 10%), and (3) negative responders (R−; TAG increase > 10%) representing 87/130 (67%), 24/130 (18%), and 19/130 (15%) of the study samples, respectively. There were no phenotypic differences for age, sex, body-mass index, glycemia, or ApoB concentrations. Sparse partial least squares discriminant analysis separated the three phenotypes with component 1 attributed to changes in TAG 50–53: X with 0–3 desaturations with R + having reductions in these TAG. Separation along component 2 identified lower mass TAG 46–48: X with 1–3 desaturations likely containing 14:0. This latter effect impacted mostly NR and R- phenotypes. Analysis of individual TAG species per response phenotype revealed TAG species that did not align with the overall TAG response phenotype. Using the TAG response phenotype for grouping, we performed SPLDA analysis for CE responses. We observed that distinction of the TAG response phenotypes qualitatively applies to CE in which separation along component 1 (65% of variance) was due to differences in CE 18:0, 18:1, and 14:0. CE 20:5 was elevated equally (>300%) between all phenotypes indicating LCn-3 intake. However, CE 22:6 was elevated R− (86%) to a greater extent vs. Res+ (55%) and NR (49%) phenotypes. Conclusions: Our data identify lipidomic signatures (TAG and CE) associated with LCn-3 response phenotypes in humans and provide insight into the variability of lipid metabolism in humans. Funding Sources: USDA-NIFA, USDA-ARS and CIHR MOP-229, 488.